Correlation of hemoglobin with creatinine clearance, antioxidant status, lipid peroxidation and ceruloplasmin in patients with chronic kidney disease - V., Sheeba; P., Arun Kumar; P. K., Swarnalatha (International Journal of Research in Medical Sciences, 2016)
Background: Anaemia in CRF is caused primarily by a combination of depressed erythropoiesis and shortened erythrocyte lifespan caused by oxidative stress. Therefore, the present study was designed to investigate the correlation between Hb concentration and antioxidant and lipid peroxidation levels. Methods: The study group consisted of 50 patients with chronic kidney disease who were on conservative treatment with the age group of 20 to 60 years. Based on the creatinine clearance values the patients were assigned in to 3 groups; Stage 3, Stage- 4 and Stage- 5 as per NKF DOQI guidelines. Control group consisted of 50 age and sex matched, non-diabetic, non-smoker healthy volunteers. About 5 ml of blood was collected and serum was used for the estimation of superoxide dismutase, ceruloplasmin and malondialdehyde and haemoglobin level using standard methods. The correlations between the different groups are performed by applying Pearson’s correlation test. The p value of ≤0.05 was taken as the level of significance. Results: A positive correlation of Hb with creatinine clearance (r=0.46, p=0.001), SOD level(r=0.4, p=0.009), serum ceruloplasmin (r=0.3, p=0.07) was observed. Significant positive correlation was found between creatinine clearance and SOD level (r=0.4, p=0.008), ceruloplasmin (r=0.3, p=0.04). A negative correlation was obtained between serum malondialdehyde levels and haemoglobin concentration (r=-0.4, p=0.007) and between creatinine clearance and MDA levels (r=-0.4, p=0.01). Conclusions: The study provides a better understanding of the biochemical parameters underlying anaemia in chronic kidney disease. The increased production of ROS and deficiency of antioxidant enzymes altered the oxidant and antioxidant equilibrium in the plasma of CKD patients.